TEKANAN WAKTU, LOCUS OF CONTROL, DAN ETIKA PROFESI: MENGUAK DIMENSI KOMPLEKS PERILAKU AUDITOR DALAM SISTEM AUDIT MODERN - Nurlatifah, Siti (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2025)
This study aims to analyze the influence of time budget pressure, locus of control, and professional ethics on auditors' dysfunctional behavior at Public Accounting Firms (KAP) in Bekasi, Indonesia. A quantitative approach was employed using a survey method, involving 40 auditor respondents selected through a purposive sampling technique. Data was collected via questionnaires that have been validated for reliability and validity and analyzed using multiple linear regression. The results reveal that time budget pressure and locus of control positively and significantly impact auditors' dysfunctional behavior. Auditors with an external locus of control are more vulnerable to dysfunctional behavior, especially under intense time budget pressure. Conversely, professional ethics showed no significant effect on dysfunctional behavior. This study provides theoretical contributions by exploring the interaction between work pressure, individual characteristics, and professional ethics in shaping auditor behavior, offering novel insights within the Indonesian auditing context. Practical implications include recommendations for Public Accounting Firms to effectively manage work pressure, strengthen auditors' internal locus of control, and enhance training programs on professional ethics. These findings are expected to support improvements in audit quality and enrich the literature on auditors' professional behavior in competitive regions like Bekasi.